2016
DOI: 10.1080/15533174.2016.1149723
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structures, and biological activity of zinc(II) complexes derived from 2-amino-1,3,4-thiadiazole derivatives

Abstract: Two new similar zinc(II) complexes, [ZnCl 2 L1 2 ] and [ZnCl 2 L2 2 ] derived from the 2-amino-1,3,4-thiadiazole derivatives, were prepared and structurally characterized by X-ray diffraction. The Zn atom in each complex has a tetrahedral coordination and is coordinated by two N atoms of the ligands and two Cl atoms. The urease inhibitory activities of the complexes and the ligands were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies of inhibitory activities performed for ligands 21 and 22, as well as metal complexes 23 and 24 at a concentration of 100 μg/mL showed that, compared to acetohydroxamic acid as a reference (92.34% inhibition), ligand 21 is a weak urease-inhibitor (4.30% inhibition), whereas ligand 22 did not inhibit urease at all. Increased activity was observed for complexes 23 and 24, with inhibition values of 14.31% and 17.8%, respectively, suggesting that metal complexes may enhance biological activity and this strategy can be used for the development of new enzyme inhibitors[45].…”
mentioning
confidence: 98%
“…Studies of inhibitory activities performed for ligands 21 and 22, as well as metal complexes 23 and 24 at a concentration of 100 μg/mL showed that, compared to acetohydroxamic acid as a reference (92.34% inhibition), ligand 21 is a weak urease-inhibitor (4.30% inhibition), whereas ligand 22 did not inhibit urease at all. Increased activity was observed for complexes 23 and 24, with inhibition values of 14.31% and 17.8%, respectively, suggesting that metal complexes may enhance biological activity and this strategy can be used for the development of new enzyme inhibitors[45].…”
mentioning
confidence: 98%